PHOSPHORUS AND ROOT DISTRIBUTION AND CORN GROWTH AS RELATED TO LONG-TERM TILLAGE SYSTEMS AND FERTILIZER PLACEMENT - Sérgio Ely Valadão Gigante de Andrade Costa (Revista Brasileira de Ciência do Solo, 2009)
Soil and fertilizer management during cultivation can affect crop productivity and profitability. Long-term experiments are therefore necessary to determine the dynamics of nutrient and root distribution as related to soil profile, as well as the effects on nutrient uptake and crop growth. An 18-year experiment was conducted at the Federal University of Rio Grande do Sul State (UFRGS), in Eldorado do Sul, Brazil, on Rhodic Paleudult soil. Black oat and vetch were planted in the winter and corn in the summer. The soil management methods were conventional, involving no-tillage and strip tillage techniques and broadcast, row-and strip-applied fertilizer placement (triple superphosphate). Available P (Mehlich-1) and root distribution were determined in soil monoliths during the corn grain filling period. Corn shoot dry matter production and P accumulation during the 2006/2007 growing season were determined and the efficiency of P utilization calculated. Regardless of the degree of soil mobilization, P and roots were accumulated in the fertilized zone with time, mainly in the surface layer (0-10 cm). Root distribution followed P distribution for all tillage systems and fertilizer treatments. Under no-tillage, independent of the fertilizer placement, the corn plants developed more roots than in the other tillage systems. Although soil tillage systems and fertilizer treatments affected P and root distribution throughout the soil profile, as well as P absorption and corn growth, the efficiency of P utilization was not affected.